The Contact-System Dependent Plasminogen Activator from Human Plasma: Identification and Characterization - Binnema, D J; Dooijewaard, G; van Iersel, J J L; Turion, P N C; Kluft, C (Thrombosis and Haemostasis, 1990)
Apart from tissue-type plasminogen activator (t-PA) and urokinase-type plasminogen activator (u-PA), a third PA appears to occur in human plasma. Its activity is initiated when appropriate triggers of the contact system are added, and the activation depends on the presence of factor III and prekallikrein in plasma. The activity of this, so-called, contact-system dependent PA accounts for 30% of the PA activity in the dextran sulphate euglobulin fraction of plasma and was shown not to be an intrinsic property of one of the contact-system components, nor could it be inhibited by inhibitory antibodies against t-PA or u-PA. We have succeeded in identifying this third PA in dextran sulphate euglobulin fractions of human plasma. Its smallest unit (SDSPAGE) is an inactive 110 kDa single-chain polypeptide which upon activation of the contact system is converted to a cleaved, disulphide-bridged molecule with PA activity. The native form, presumably, is an oligomer, since the apparent M. on gelchromatography is 600,000. The IEP is 4.8, much lower than that of t-PA and u-PA. Although the active 110 kDa polypeptide cannot be inhibited by anti-u-PA, it yet comprises a 37 kDa piece with some u-PA related antigenic determinants. However, these determinants are in a latent or cryptic form, only detectable after denaturation by SDS. The 110 kDa polypeptide is evidently not a dimer of 55 kDa u-PA or a complex of u-PA with an inhibitor. It is probably a PA derived from a gene quite distinct from that of t-PA or u-PA, but sharing some homology with u-PA. The physiological role of this contact-system dependent PA remains to be established